Pengaruh Fasilitas dan Atraksi terhadap Kepuasan Pengunjung di Marcopolo Water Adventure Bogor - Visya Putri Annisa; Taufiq Kurniawan (Yayasan Literasi Sains Indonesia, 2024)
The city of Bogor has a water tourist attraction, namely Marcopolo Water Adventure Bogor. The current condition has problems with facilities and attractions, which has an impact on visitor satisfaction where the available facilities and attractions receive less attention from Marcopolo Water Adventure Bogor, thus causing visitors to feel less comfortable when carrying out activities at the tourist spot, thus affecting the feelings they feel. caused by visitors. The purpose of this research is to determine the influence of facilities and attractions on visitor satisfaction at Marcopolo Water Adventure Bogor. This research uses quantitative methods with a sample of 100 visitors. This sampling technique uses purposive sampling. The data used a designed questionnaire. The data analysis method used is multiple regression analysis. The research results show that facilities and attractions influence visitor satisfaction with a significant value of 0.000 < 0.05. With the determination test results, 53.3% is influenced by this variable and the rest is influenced by other variables. The conclusion is that these changes will help visitor satisfaction by providing more facilities and more attractions to meet visitors' needs while carrying out activities at the place.